The prognostic relevance of psychological factors with regard to participation and success in table-tennis - Martinent, G.; Cece, V.; Elferink-Gemser, M. T.; Faber, I. R.; Decret, J.-C. (Journal of Sports Sciences, 2018)
This study examined the prognostic relevance of self-determined motivation, coping, burnout, perceived stress and recovery experienced by 159 youth table-tennis players involved in intensive training centers with regard to their participation and success six years later. Results of ANCOVAs showed that players who still practiced at time 2 (T2; six years later; n = 130) reported lower time 1 (T1; while they were involved in intensive training centers) amotivation (large effect), disengagement-oriented coping, sport devaluation and reduced accomplishment (moderate effects) than their counterparts who dropped out at T2 (n = 29). Results of ANCOVAs also showed that international (n = 18) and/or national players (n = 86) at T2 reported significantly lower T1 amotivation (large effect), disengagement-oriented coping and sport devaluation (moderate effects) in comparison to regional (n = 26) players at T2. Finally results of correlational analyses showed that T2 performance and/or six-year performance progress were significantly and weakly correlated with introjected and external regulations, perceived stress and perceived recovery, and significantly and moderately correlated with amotivation, disengagement-oriented coping, sport devaluation, and reduced accomplishment. Overall, this study provided insights into the role played by self-determined motivation, coping, burnout, perceived stress and recovery in the table-tennis players` dropout and performance level six years later.